Effects of a visual novel-based learning object on learners' performance in an eSkwela classroom - Cruz, Aaron Paul C. (College of Education, University of the Philippines Diliman, 2018)
This study aimed to develop a visual novel learning object to be used in the alternative learning system (ALS) eSkwela classroom in Barangay Loyola Heights, Quezon City. This study presented four research questions: (1) What are the needs of the learners in the eSkwela classroom to enhance learning? (2) How will the visual novel learning object be designed? (3) Is there a difference in the pre-test and post-test scores of the learners in the eSkwela classroom? and (4) What category in the learning object evaluation of the visual novel learning object contributed to effective learning in the eSkwela context?